PERANAN MEKANISME PENYELESAIAN SENGKETA UNTUK MENDUKUNG VISI INDONESIA 2030 - -, Supriyanta - (ipsojure, 2009)
AbstrakIndonesia’s development in the future will be based on the long-term Indonesianvision 2030 wich is the realization of a modern Indonesian nation and state which issafe, peaceful, just, democratic and prosperous, upholding the values of humanity,independence and the unity and the 1945 Constitution. The Indonesia’s developmentin 2030 is directed towards a) the realization of a life of a society, nation and statethat is safe, unified, harmonious and paceful;b) the realization of a society, nationnad state that upholds the law, equality and human right; c) the ralization of aneconomy capable of providing work opportunities, reasonable living and a strongfoundation for sustainable develepment .alternative Dispute Resolution(ADR)interpreted as alternative to adjudication or alternative to litigation. If we use thefirst interpretation, arbitration cannot be part of ADR as arbitration is anadjudication in nature. The second interpretation can include arbitration as a part ofCDR as it is not a litigation or court process. However, ADR has been developedrapidly in all part of theworlds as it has a flexibility and its ability to respond tomerely substantive interest (tangble/proprietary related interest) but alsopsychological and procedural interest as three of them are basic human interest.